Pengaruh Praktik Kewirausahaan dan Ekspektasi Pendapatan terhadap Minat Berwirausaha Siswa SMK Negeri 62 Jakarta - Abdullah Azzam; Henry Eriyanto; Maulana Amirul Adha (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The unemployment rate in Indonesia remains relatively high, particularly among vocational high school (SMK) graduates, who have the highest open unemployment rate. This condition indicates an imbalance between the skills possessed by graduates and the needs of the workforce. One strategy that can be taken to address this problem is to encourage the emergence of new entrepreneurs. Interest in entrepreneurship is a key factor that can motivate individuals, especially students, to create jobs for themselves and others. To foster this interest, motivating factors such as adequate entrepreneurial practices and realistic income expectations are needed. This study aims to analyze the contribution of entrepreneurial practices and income expectations to increasing student entrepreneurial interest. A quantitative approach was used in this study, with primary data collection through an online survey assisted by Google Forms. The research instrument was designed using a Likert scale to measure respondents' perceptions. Sampling was determined using a proportional random sampling technique based on the Taro Yamane formula, resulting in 188 students as study respondents. Data analysis was performed using Smart PLS software to test direct and indirect relationships between variables. The results showed that entrepreneurial practices have a direct, positive, and significant influence on entrepreneurial interest. Furthermore, entrepreneurial practice also has a direct, positive, and significant effect on income expectations. Furthermore, it was found that entrepreneurial practice has an indirect, positive, and significant impact on entrepreneurial intentions through the mediation of income expectations. These findings indicate that students who gain direct experience in entrepreneurial practice will have a clearer picture of the potential income that can be obtained, thus increasing their motivation to become entrepreneurs.